AN ANALYSIS OF STUDENTS’ READING SPEED OF RECOUNT TEXT AT X GRADE SMK PLUS KARYA BAKTI PERTIWI - Nuraeni, Resti; Syathroh, Isry Laila; Gunawan, Aep (IKIP Siliwangi, 2024)
This research analyzes students’ reading speed of recount text at tenth-grade students of SMK Plus Karya Bakti Pertiwi. The researchers used qualitative descriptive method to analyze the data. The subject of this research was 30 students of eleventh-grade students in SMK Plus Karya Bakti Pertiwi. The instrument in this research was a reading test of recount text. The researchers used a stopwatch to count the time while students were reading the text. Based on the reading speed test, the typical speed of reading students revealed that three students could read 100-149 words per minute (wpm) in slow category, and other 27 students can only obtain 50-99 wpm in very slow category. In summary, the skill of reading speed students at X grade in SMK Plus Karya Bakti Pertiwi was very slow.